Enhancing Communication and Collaboration Skills in Social Studies and Life Skills Education Learning through Presentations (Journal of Vishwa Adarsha College, 2025)
This study aims to explore secondary-level (Grade 11 and 12) students’ experiences with oral presentation to develop their communication and collaboration skills in social studies and life skills education. Oral presentation is a teaching and learning approach where the learners are involved in delivering the content through discussion and presenting it interactively in the classroom. The purposive sampling technique was used to choose the participants following a narrative inquiry as the research methodology. Ten participants from Grade 11 were selected and involved in oral presentations and interviews to explore their experiences. The same participants continued oral presentations in grade 12 and participated in Focus Group Discussion (FGD) and interviews to unveil their experiences and perspectives on the roles of oral presentations to enhance communication and collaboration skills. The data collected through two rounds of semi structured interviews and FGD were transcribed and coded, and categorized to generate four main themes: interaction for meaningful learning, harmonious understanding for contextual learning, synergy in connection and growth with creativity, and challenges in oral communication in group learning were generated. The major findings of the study revealed that oral presentation is useful to enhance the soft skills, especially communication and collaboration, of learners to promote lifelong learning. Social studies and life skills education need teachers to use multiple innovative pedagogical approaches for effective teaching and learning, which can foster knowledge, skills, attitudes, and values among the learners. This process prepares them as global, civilized, and democratic citizens in the future.